KOMPETENSI PROFESIONAL PENGUASAAN MATERI DAN PENGEMBANGAN GURU SDN 10 LANGKAI PALANGKA RAYA - Aisyah Noraynah; Anis Wulandari; Aprizal Kumaunang; Dwi Andika Lestari; Noor Fitriah (STKIP Subang, 2026)
This study aims to describe teacher professional competence in mastering material and self-development at SDN 10 Langkai. The study used a descriptive qualitative approach with data collection techniques through interviews and documentation. The subjects were teachers at SDN 10 Langkai who were directly involved in the learning process and professional development activities. The results indicate that teachers have demonstrated good professional competence in mastering material by understanding learning objectives, adapting material to students' abilities, using simple language, and relating learning to students' daily lives. Teachers also implement differentiated learning and utilize technology such as social media, LCDs, interactive TVs, learning videos, and digital platforms in the learning process. In terms of self-development, teachers actively participate in seminars, training, and workshops, both online and offline, to improve the quality of learning. Factors supporting teacher professional competence include school support, the availability of learning media, and technological advances. Inhibiting factors faced by teachers include limited time for self-development activities and difficulties in adapting learning language to ensure it is easily understood by elementary school students. With good professional competence, teachers are expected to be able to create effective, creative, innovative learning that is tailored to students' needs.